1998
DOI: 10.1001/archotol.124.8.921
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Amoxicillin and Clavulanate Every 12 Hours vs Every 8 Hours for Treatment of Acute Bacterial Maxillary Sinusitis

Abstract: Amoxicillin and clavulanate given every 12 hours is as effective and as safe as administration every 8 hours for the treatment of acute bacterial maxillary sinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The low efficacy of amoxicillin/ potassium clavulanate found in these studies could possibly be thus in part due to random error, and not an accurate measure of the efficacy of the antibiotic used. The efficacy of amoxicillin/potassium clavulanate found in the other 5 studies ranged from 74.5% -93% (11,17,21,23,25) , suggesting that the true efficacy of amoxicillin/potassium clavulanate is probably closer to 80%. In general, between studies, we note that there is a big variation of efficacy and side effects even just within the same drug, and in the future we need more standardized studies to be able to have better evidence on the efficacy and side effects of various drugs used in the treatment of ARS.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The low efficacy of amoxicillin/ potassium clavulanate found in these studies could possibly be thus in part due to random error, and not an accurate measure of the efficacy of the antibiotic used. The efficacy of amoxicillin/potassium clavulanate found in the other 5 studies ranged from 74.5% -93% (11,17,21,23,25) , suggesting that the true efficacy of amoxicillin/potassium clavulanate is probably closer to 80%. In general, between studies, we note that there is a big variation of efficacy and side effects even just within the same drug, and in the future we need more standardized studies to be able to have better evidence on the efficacy and side effects of various drugs used in the treatment of ARS.…”
Section: Discussionmentioning
confidence: 91%
“…For amoxicillin/potassium clavulanate, the efficacy ranges from 50% to 93% (11,21,(23)(24)(25)34) . One reason for the large range could be due to the 2 studies by Wald et al (24,34) , which had small sample sizes of 28 patients in each study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five clinical trials (Table 1) in adults [7][8][9][10][11], involving over 2100 patients, compared the bacteriological and clinical efficacy of the BD and TID doses of amoxicillin/clavulanate. No significant difference was seen between the BD and TID regimens in the bacteriological and clinical success rates in any of the infections.…”
Section: Clinical Trials In Adultsmentioning
confidence: 99%
“…The efficacy of amoxicillin/potassium clavulanate ranged from 50% to 93%. All studies (11,17,21,(23)(24)(25) used a dosing regimen of 500/125 mg thrice a day for 10 to 14 days. Most studies reported quite a high incidence of minor adverse effects, with 3 studies reporting a side effect rate of more than 40% (21,23,24) .…”
Section: Cefuroxime Axetil (Figure 1)mentioning
confidence: 99%